A global analysis of the impact of zero‐tillage on soil physical condition, organic carbon content, and plant root response - Mondal, Surajit; Chakraborty, Debashis; Bandyopadhyay, Kalikinkar; Aggarwal, Pramila; Rana, Dharamvir Singh (Wiley, 2020)
Food security involves the sustainable utilization of soil and land resources. Zero‐tillage (ZT) practice is a proponent of better resource utilization, to improve soil physical condition, and a potential sink to atmospheric carbon. However, the impact varies across climates, over the ZT history, cropping systems, and soil depths. A meta‐analysis was performed, based on 4,131 paired data from 522 studies spread globally, to evaluate the effect of ZT in comparison to conventional tillage, on soil physical condition (bulk density; mean weight diameter of aggregates; field capacity water content; and steady‐state infiltration rate), soil organic carbon (SOC) content, and the root response (root length density). Zero‐tillage significantly improved mean weight diameter of aggregates and field capacity water content at surface and subsurface layers by 19–58% and 6–16%, respectively, and resulted in no change in bulk density in either of the layers, but infiltration rate increased by 66%. Surface 0‐ to 5‐ and 5‐ to 10‐cm layers had significantly higher SOC content under ZT, whereas in other layers, the SOC content either reduced or did not change, resulting in a small and insignificant variation in the SOC stock (~1.1%) in favor of ZT. The root length density improved by ~35% in ZT only at 0‐ to 5‐cm soil depth. Effect of climate, soil type, or cropping system could not be broadly recognized, but the impact of ZT certainly increased over time. Improvements in soil aggregation and hydraulic properties are highly convincing with the adoption of ZT, and therefore, this practice leads to the better and sustainable use of soil resources.